The effects of the first wave of COVID-19 restrictions on physical activity: a longitudinal study from "step into health" program in Qatar - Abdulla S. Al-Mohannadi; Abdulaziz Farooq; Ahmad Salman; Ahmad Salman; Amine Ghram; Amine Ghram; Amine Ghram; Sanaa T. Al-Harahsheh; Lina Majed; Suzan Sayegh; Marco Cardinale; Marco Cardinale; et al. (Frontiers Media S.A., 2024)
IntroductionThe COVID-19 pandemic led to restrictions that prevented physical activity in public places. This study sought to conduct a comprehensive longitudinal analysis of how lockdown policies in an Arabian Gulf country influenced the patterns of physical activity during first wave.MethodsIn a longitudinal study design, members of the ongoing "Step into health" community-based health promotion program who provided valid pedometer data from January to August 2020, covering pre, during and post-covid first wave period met the inclusion criteria.Results420 (76.7% men, 13.8% ≤40 years) were included in the study. Overall, significant decline in daily step counts was recorded (−1,130 ± SE302) after the implementation of lockdown policies (p < 0.001). When the restrictions were removed, the steps per day were still lower compared to pre-covid for men (−910 ± SE610, p = 0.017) and among individuals with normal BMI (−1,304 ± SE409, p = 0.004). The lockdown in Qatar did not significantly affect women and individuals with obesity who already had lower daily steps pre-covid.DiscussionThe present study confirms immediate decline in daily steps imposed indirectly through the COVID-19 lockdown measures. Participants with higher physical activity levels pre-covid experienced significant decline in step count during and even after restrictions were uplifted.